(untitled) (Medical Forum Monthly, 2023)
Objective: The objective of this study was to determine the risk factors and local complications with outcome of acute pancreatitis in tertiary referral center. Study Design: Descriptive study. Place and Duration of Study: This study was conducted at the Department of Hepatology / Emergency, Asian Institute of Medical Sciences, Hyderabad from January 2021 to May, 2022. Materials and Methods: All consecutive patients with acute pancreatitis over the age of 10. Ultrasound based GB stone, CBD dilatation and type of pancreatitis (interstitial and necrotic) were expressed in percentages. Outcomes (death of patient or improved and discharged) and etiologies were also calculated in percentages. Stratification with respect to age, gender, DM, Alcohol, CBD stone, GB stone, Type of pancreatitis CBD dilatation and Ascites (Present/absent) were performed. Results: A total of 91 patients were enrolled, The Mean age of the study population was 40.22 ±15.657 years (range: 13–75 years) and majority were female 49(53.8%). There were 45(49.5%) patient with normal basal mass index (BMI) followed by 35(38.5%) patient was obese, 9(9.9%) were overweight and 2(2.1%) were underweight. 44(48.4%) were idiopathic while Gall stones was found in 33(36.3%) patients and alcoholism in 9(9.9%) patients. Pancreatic collection was the common complication in 12(13.2%) patients, these cases were identified as acute pancreatitis. When risk factors and local complication were associate with outcome, the p value < 0.02 was significant only for local complication while there was no significant association with any risk factors Conclusion: The findings of this study indicate that more studies need to be undertaken to determine the obesity paradox and the relationship between risk factors and outcomes.